Efficient navigation of medical mega-images (2010)
Recientes avances en la tecnología de imagen médica han permitido la adquisición de grandes volúmenes de datos visuales. Esto ha impuesto nuevos requerimientos de interacción a los médicos. El desarrollo de dichos mecanismos es un reto de investigación inexplorado. Esta tesis se dedica al estudio de los procesos complejos que subyacen en los eventos producidos cuando un medico interactúa con un gran volumen de datos, y como puede mejorarse esta interacción. Nuestra meta es proveer mecanismos para obtener información significativa en tiempos mínimos. Para lograr esto, se formularon estrategias originales para inferir y sintetizar conocimiento medico a partir de estos datos. Nuestra inspiración son los mecanismos biológicos que controlan la exploración visual de los datos y sus movimientos complejos. Los métodos propuestos fueron exitosamente aplicados en la mejora de las velocidades de navegación en microscopía virtual. Recent advances in imaging technology have provided large volumes of image data. This has imposed novel interaction requirements to medical doctors. Development of these interaction mechanisms is a challenging unexplored research problem. This thesis was devoted to the study of the complex processes underlying the events produced when a medical user interacts with a large volume of medical data, and how can be improved interaction by using this information. Acquirement of medical knowledge from these data implies intensive interaction. Our aim was to provide mechanisms for obtaining significant information during this interaction in a minimal time. To achieve this, we proposed original strategies for inferring and synthesizing medical knowledge from these data. Our inspiration was the biological mechanism that controls the visual data exploration and the complex movements involved in the navigation task. Proposed methods were successfully used to improve navigation velocities in virtual microscopy and to increase the tracking capabilities of the complex human motion.